Social support and self-management activation among older adult chronic disease patients in China: the chain mediating role of acceptance of illness and fatigue - Zhang, Shi Qing; Deng, Man; Xu, Xue Jun; Yang, Yue; Zhao, Shuang; Yue, Jianxin; Chen, Yong Xia; Wang, Fu Zhi; Yang, Xiumu (Frontiers in Public Health, 2025)
BackgroundWith the rapid aging of the global population and the continuous increase in the incidence of chronic diseases among the older adult, self-management activation has become a key factor in improving patients’ quality of life. This study examines the relationship between social support and self-management activation in older adult patients with chronic diseases, with a focus on the mediating roles of illness acceptance and fatigue within this framework.MethodsA convenience sampling method was employed to recruit 317 older adult patients with chronic diseases from three communities in Hefei, Anhui Province, China, between August and November 2023. Data collection involved the use of a general information questionnaire, the Illness Acceptance Scale, the Self-Rating Social Support Scale, the Chinese version of the Multidimensional Fatigue Inventory, and the Public Health Activation Index Scale. The influencing factors were examined through independent t-tests, one-way ANOVA, and Pearson correlation analysis in SPSS 26.0. Additionally, a structural equation model (SEM) in AMOS 26.0 was employed to evaluate the possible mediating roles of acceptance of illness and fatigue in the connection between social support and self-management activation.ResultsA strong positive relationship was observed between social support, acceptance of illness, and Self-management activation (r = 0.615 and 0.787, p < 0.01). In contrast, a significant negative correlation was observed between fatigue and self-management activation (r = −0.695, p < 0.01). Further analysis using structural equation modeling (SEM) demonstrated that the model exhibited a good fit (RMSEA = 0.076, p < 0.05). The results indicated that acceptance of illness and fatigue significantly mediate the connection between social support and self-management activation. Mediation effect analysis revealed that the direct impact of social support, acceptance of illness, and fatigue on self-management activation accounted for 24.2% of the overall effect. In comparison, the indirect effects made up 75.8%.ConclusionThis study demonstrates that the Self-management activation of older adult adults with chronic conditions is generally low and may be influenced by various individual and environmental factors. The findings highlight that enhancing acceptance of illness and alleviating fatigue symptoms are crucial intervention strategies to improve Self-management activation, particularly for patients with low levels of social support.